Nonbacterial thrombotic endocarditis in a patient with primary antiphospholipid syndrome. Issue 6 (25th June 2018) - Sirinvaravong, Natee; Rodriguez Ziccardi, Mary C; Patnaik, Soumya; Shah, Mahek; Fernandez, Gustavo; Aliling, Jose-Nitram; Rubin, Alexander
Abstract: Nonbacterial thrombotic endocarditis (NBTE) is described in patients with mucin-producing cancers and connective tissue disorders (usually SLE). We report NBTE in the setting of primary antiphospholipid antibody syndrome (APS). A 65-year-old female with APS was incidentally found to have thickened mitral leaflets on transthoracic echocardiogram with no signs of infection. Transesophageal echocardiogram (TEE) showed a mobile mitral mass (1.4 × 0.7 cm) and moderate mitral regurgitation. Differential diagnoses included bacterial endocarditis, NBTE, thrombus or tumor. Given the history of primary APS, the absence of fever and negative blood cultures, NBTE was considered. Low-molecular-weight heparin, hydroxychloroquine and corticosteroid were initiated. Repeat TEE in a week revealed shrinkage of the mass (0.6 × 0.7 cm), indicating an inflammatory nature. Lifelong anticoagulation is indicated regardless of embolism occurrence. Hydroxychloroquine and corticosteroids may have roles in the treatment. Determining and treating the underlying etiology is important.